Effectiveness of Islamic Law in Protecting The Copyright of Indigenous Peoples of Indonesia in The Form of Traditional Knowledge & Traditional Cultural Expressions - Mulhimmah, Baiq Ratna; Olagunju, Ridwan (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Copyright Protection of Indonesian Indigenous Peoples in the form of Traditional Knowledge (TK) &Traditional Cultural Expression (TCE) currently does not meet the sense of justice. The state is obliged to provide comprehensive protections capable of guarding the rights of Indigenous peoples under an adequate legal umbrella. Because the existence of Indigenous peoples, along with copyrights in the form of TK & TCE is part of the wealth and identity of the nation, this research focuses on how the view of Islamic law (Legal Opinion of Indonesian Ulama Council No.1 of 2003 concerning Copyright and Legal Opinion Of Indonesian Ulama Council No.1 of 2005 concerning Intelectual Property Right) with the maqasid al Shari’ah approach in protecting the rights of indigenous peoples. Islamic law is one of the secondary legal materials in determining state law and is expected to strengthen in providing solutions to this problem. The research method is normative with a concept and case approach to conclude that Islamic law (legal Opinion Of Indonesian Ulama Council) with the Maqasid al Shari’ah approach in protecting Traditional Knowledge (TK) &Traditional Cultural Expression (TCE) is a must. This is based on an obligation order covering several matters, including; the protection of life and hifzul nafsi/hifzul ‘irdhi, protection of reason (hifzul aqli), and protection of property (hifzul maal).